Leading Reflective Practices in Montessori Schools - Sharon Damore; Barbara Rieckhoff (University of Kansas, 2021)
In this paper, we report the results of a qualitative study examining the development of leadership competencies as Montessori school leaders gain experience using a coaching protocol with their teachers. Extending previous work, the emphasis is on the school leaders' specific roles as instructional supervisors leading reflective practices. National standards, both traditional and Montessori, are a foundation to investigate a group of Montessori school leaders' development in reference to articulated competencies, specifically for the school leader to tend to their own learning and effectiveness through reflection, study, and improvement, and to empower teachers to the highest levels of professional practice and to continuous learning and improvement. After the use of a prescribed coaching protocol, 12 Montessori school leaders from 6 schools across the United States were interviewed using a set of semistructured questions. The study results support that reflective practices lead to both improvement of practice with this group of Montessori school leaders and their respective teachers. We conclude that self-reflection is critical to a Montessori leader's success, empowering them to model and influence reflective practices, with direct impacts on teacher reflection and school improvement. This conclusion becomes relevant as we observe our Montessori school leaders assuming numerous and complicated administrative roles, from management and teacher evaluation to instructional supervision, mentoring, and coaching teachers.